2003
DOI: 10.1073/pnas.252643299
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of low-molecular weight heparins with improved in vivo activity

Abstract: Heparin and low-molecular weight heparins (LMWHs), complex, sulfated polysaccharides isolated from endogenous sources, are potent modulators of hemostasis. Heparin and LMWHs interact with multiple components of the coagulation cascade to inhibit the clotting process. Pharmaceutical preparations of these complex polysaccharides, typically isolated from porcine intestinal mucosa, are heterogeneous in length and composition and, hence, highly polydisperse. Because of the structural heterogeneity of heparin and LM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 34 publications
0
47
0
Order By: Relevance
“…16,41 In this regard, a small uncontrolled study concluded that minidose UFH could reduce the frequency of sickle cell pain crises. 76 While the potential side effects and requirement for injectable administration limit the therapeutic potential of UFH for preventing painful sickle cell vasoocclusion, 48 more detailed molecular understandings of the structural determinants the Pselectin blocking activity 77 and the technology required to tailor heparin activities according to desired effects 78 offer promise for the future use of sulfated anionic polysaccharides for preventing painful vasoocclusion in sickle cell disease. Consideration is now warranted for this therapeutic approach to preventing pain crises in patients with sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%
“…16,41 In this regard, a small uncontrolled study concluded that minidose UFH could reduce the frequency of sickle cell pain crises. 76 While the potential side effects and requirement for injectable administration limit the therapeutic potential of UFH for preventing painful sickle cell vasoocclusion, 48 more detailed molecular understandings of the structural determinants the Pselectin blocking activity 77 and the technology required to tailor heparin activities according to desired effects 78 offer promise for the future use of sulfated anionic polysaccharides for preventing painful vasoocclusion in sickle cell disease. Consideration is now warranted for this therapeutic approach to preventing pain crises in patients with sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its widespread use, native, unfractionated heparin has many limitations, such as interpatient variablility, nonspecific protein binding, unstable pharmacokinetics, and potential side effects such as hemorrhage and heparin-induced thrombocytopenia (11). The variability of heparin arises from its complex molecular structure, intrinsic polydisperity (molecular mass ranges from 3 to 30 kDa) and heterogeneity of samples (only one in three molecules contains the active AT-III-binding site) (12).…”
mentioning
confidence: 99%
“…An anti-Xa assay was performed by modification of the amidolytic method (17) with a Coatest heparin test kit by using S-2222 as the chromogenic substrate (Diapharma Group, West Chester, OH). The detailed procedure has been described (15).…”
Section: Methodsmentioning
confidence: 99%
“…The antithrombotic effects of inhaled LMWH were evaluated by Wessler's stasis model (18) adapted for the rat by using Russell Viper Venom as the thrombogenic stimulus (19). The procedure was performed as described (15). Briefly, 1 h after pulmonary inhalation or s.c. injection of LMWH, a laparot- …”
Section: Methodsmentioning
confidence: 99%